Dioctophyma renale in Dog’s Testicle - Regalin, Bruna Ditzel da Costa (2016)
Background: Dioctophyma renale is a giant worm, nematode parasite, which infest dogs, rarely humans or other domestic and wild species. The life cycle is complex and infestation occurs by ingestion of aquatic oligochaete (annelid), fsh and frogs. This nematode normally installs in the right kidney of dog, however, there are reports of ectopic migration, such as, for example, in the stomach, abdominal cavity, liver, bladder, ureters, urethra, scrotum, uterus, ovaries, mesenteric lymph nodes, mammary gland, thoracic and pericardial cavity. The aim of this work is to report the location of erratic Dioctophyma renale in the left testicle of a dog. Case: A mongrel dog, about 4 years old, weighing 7.7 kg, rescued from the street after being hit by a car was admitted at the Veterinary Clinical Hospital of CAV / UDESC. Clinical examination showed no signifcant changes, except for the crackling of pelvic bones, suggesting pelvic fracture. Pelvic radiography and abdominal ultrasound were requested, and complete blood count as pre-anesthetic evaluation was performed. The blood count showed leukocytosis with neutrofilia with a regenerative left shift. The patient was referred for pelvic fxation and in the same procedure orchiectomy was performed. The premedication was acepromazine 0.05 mg/kg and morphine 0.5 mg/kg, administrated intramuscularly. Anesthesia was induced with propofol and maintained with isoﬂurane inhalation. Epidural anesthesia was performed with bupivacaine 0.26 mL/kg combined with morphine 0.1 mg/kg. During surgery it was noted that the left testicle presented itself deformed. The material has been collected and sent for histopathological analysis. In this analysis the presence of a male specimen of Dioctophyma renale, inside the testicle, with focal cavity formation was observed, indicating destruction of testicular parenchyma surrounded by moderate infltrate of macrophages and plasma cells, suggesting parasitar orchitis. In abdominal ultrasound no evidences of abnormalities such as nephropathy were observed and no evidence of the presence of another Dioctophyma renale in kidney or any region of the abdominal cavity were observed. Discussion: Among the many reports of ectopic locations of the mentioned nematode, no report was found related to your intratesticular migration. The confrmation was given based on morphological characteristics, color and size of the parasite (giant worm). Diagnosis usually occurs by accidental necropsy fndings or surgical fndings, and the treatment of choice is surgical removal of the parasite. Although the ultrasound is not a suitable diagnostic method for dioctophymosis in dogs, it can show kidney destruction compatible with the disease. In this case, abdominal ultrasonography demonstrated no presence of the parasite in the kidneys or in any region of the abdominal cavity. When there is kidney parasitism, it has parenchymal destruction, leaving only the renal capsule in advanced cases; in these cases, right kidney is more often stricken and in human beings dioctophymosis already have been reported like kidney tumor. This nematode is more often found in dogs than in cats, horses or any other domestic animal. It can be concluded that the behavior of intratesticular infestation resembles the picture observed in renal parasitism, with parenchymal destruction. The complete destruction probably should happened if orchiectomy had not been performed. Keywords: Dioctophyma renale, testicle, dog